Wyrażenia komparatywne w funkcji intensyfikatorów przestrzennej cechy parametrycznej (na materiale języków rosyjskiego i polskiego) - Chudyk, Danuta (Przegląd Rusycystyczny, 2006)
ON THE EXPRESSIONS OF COMPARISONIN THE FUNCTION OF SPATIAL MEASUREMENT FEATURES(ON POLISH AND RUSSIAN MATERIAL) Summary The article discusses fixed expressions of comparison where the basis of comparison are thespatial measurement adjectives pertaining parts of human body.The aim of the article is to:1) find out which spatial measurement adjectives may become the basis of comparison in descri-bed expressions,2) find out what can be the subject of comparison in given spatial measurement adjectives,3) determine the classes of objects of comparison that appear in fixed expressions of the typebeing described.